2018
DOI: 10.1371/journal.pone.0191506
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cervical precancerous lesions among women screened for cervical cancer in Addis Ababa, Ethiopia: A case control study

Abstract: BackgroundCervical cancer is the second most prevalent cancer among women in the developing countries including Ethiopia. Precancerous lesions can be developed and risk to the development of cervical cancer over time. Early identification of the precancerous lesion and its risk factor is paramount in preventing cervical cancer. However, the determinants of cervical precancerous lesions are not well documented in Ethiopia. Therefore, this study is conducted to determine factors associated with cervical precance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
89
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(144 citation statements)
references
References 22 publications
35
89
8
2
Order By: Relevance
“…Early onset of sexual activity is thought to be associated with high risk because, during puberty, cervical tissue undergoes physiologic changes, transformation zone on the ecto-cervix is enlarged, and exposure to HPV at such times may facilitate infection which may make this area more vulnerable to development of dysplasia, a cervical squamous precancer. In addition an earlier age of sexual debut implies a longer period of sexual activity a higher likelihood of having many sexual partners and it is inconsistent with study conducted at Addis Ababa [16]. This difference could be due to the differences in the age distribution of study populations, sexual practice or could be due to the sociocultural difference and settings.…”
Section: Discussionmentioning
confidence: 92%
“…Early onset of sexual activity is thought to be associated with high risk because, during puberty, cervical tissue undergoes physiologic changes, transformation zone on the ecto-cervix is enlarged, and exposure to HPV at such times may facilitate infection which may make this area more vulnerable to development of dysplasia, a cervical squamous precancer. In addition an earlier age of sexual debut implies a longer period of sexual activity a higher likelihood of having many sexual partners and it is inconsistent with study conducted at Addis Ababa [16]. This difference could be due to the differences in the age distribution of study populations, sexual practice or could be due to the sociocultural difference and settings.…”
Section: Discussionmentioning
confidence: 92%
“…The following items were used to appraise cross-sectional studies: [1] inclusion criteria; [2] description of study subject and setting; [3] valid and reliable measurement of exposure; [4] objective and standard criteria used; [5] identification of confounder; [6] strategies to handle confounder; [7] outcome measurement; and [8] appropriate statistical analysis. In addition, JBI Systematic Reviews checklist for case control studies (41) using ten items were used to appraise one case control study (42). Studies considered low risk whenever fitted to 50% and or above quality assessment checklist criteria's (40,43).…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…Among the total 15 studies included to the current review, five of them were from Addis Ababa City Administration (17,42,(48)(49)(50). Five studies were included from the Southern Nations Nationalities and People Region (SNNPR) (51-55).…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Parthenis et al [10] gives another reason for causes of cervical cancer is Sexually Transmitted Diseases (STDs) also leads to the same. Teame et al [11] identified that age of the women above 38 years with STD history are becoming the victims of cervical cancer. Since no symptoms of cervical cancer are known by the women at its earlier stage, its leads to their life loss Okunowo et al [12].…”
Section: Related Workmentioning
confidence: 99%